Partition member for total heat exchange element, total heat exchange element using the same, and method for manufacturing partition member for total heat exchange element
A hydrophobic porous base material with fine cellulose fibers enhances air and moisture permeability, addressing the challenge of making thinner partition members for total heat exchange elements, resulting in improved heat exchange efficiency and increased stackable layers.
Patent Information
- Application Number
- JP2024107755
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-07-03
- Publication Date
- 2025-01-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing partition members in total heat exchange elements are difficult to make thinner while maintaining high heat exchange efficiency, limiting the number of stackable layers and overall performance.
A hydrophobic porous base material with fine fibers of polymeric polysaccharides, such as cellulose, is used, with specific fiber widths and properties to enhance air and moisture permeability, allowing for a lightweight and efficient partition member design.
The partition member achieves high air permeability, moisture permeability, and carbon dioxide gas barrier properties, enabling increased stackable layers and improved heat exchange efficiency without compromising mechanical strength.
Smart Images

Figure 2025010102000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a partition member for a total heat exchange element, a total heat exchange element including the same, and a method for manufacturing a partition member for a total heat exchange element. [Background technology]
[0002] Conventionally, a heat exchange ventilation device (total heat exchanger) that exchanges heat between the intake air and the exhaust air during ventilation has been proposed as a device that can ventilate without impairing the cooling or heating effect. This total heat exchanger is widely used in which a plurality of partition members (liners) are laminated via a spacing member, an intake air path that introduces outdoor air into the room and an exhaust air path that exhausts indoor air to the outside are partitioned, and a total heat exchange element that simultaneously exchanges sensible heat (temperature) and latent heat (humidity) is incorporated.
[0003] For example, in winter, outdoor air as supply air and indoor air as exhaust air are guided into each flow path separated by a spacing member. At this time, the supply air and exhaust air exchange temperature and humidity through the partition member. The partition member through which heat exchange occurs has moisture permeability that allows water vapor to pass but not air. The partition member also has gas shielding properties due to the isolation between the supply air and exhaust air. As a result, the supply air is heated and humidified before being supplied to the room, and the exhaust air is cooled and dehumidified before being discharged outside. The partition member has both moisture permeability and gas shielding properties, thereby achieving ventilation through total heat exchange. Such partition members must have both heat conductivity and moisture permeability, and therefore in many cases, paper containing natural pulp as a main component, such as glassine paper, is used (Patent Document 1).
[0004] Furthermore, in recent years, attempts have been made to apply cellulose nanofibers, which have gas barrier properties, to partition members (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4252892 [Patent Document 2] Patent Publication No. 2021-155865 Summary of the Invention [Problem to be solved by the invention]
[0006] In light of the need to combat global warming and conserve energy, total heat exchange elements have been attracting attention. In order to further improve the heat exchange efficiency of total heat exchange elements, it is believed that it would be effective to make the partition members thinner than ever before and to increase the number of stacked layers of the total heat exchange element. However, this has been difficult to achieve with the partition members described in Patent Documents 1 and 2. [Means for solving the problem]
[0007] Means for Solving the Problems The inventors of the present invention carried out intensive research in order to provide a partition member for a total heat exchanger having excellent heat exchange efficiency, and as a result discovered a new partition member containing a hydrophobic porous base material and fine fibers of a polymeric polysaccharide having a specific fiber width, which led to the invention of the new partition member. That is, the present invention provides the following: <1> ~ <15> Regarding. <1> A hydrophobic porous substrate; The hydrophobic porous substrate contains fine fibers of polymeric polysaccharides having a fiber width of 1 to 1000 nm at least in the pores thereof, Air permeability is 10,000 seconds or more, and moisture permeability is 2,500 g / m 2 Partition material for total heat exchange elements lasting 24 hours or more. <2> The fine fibers are fine cellulose fibers. <1> The partition member for a total heat exchange element according to claim 1. <3> The fine fibers have a fiber width of 1 to 10 nm. <1> or <2> The partition member for a total heat exchange element according to claim 1. <4> The hydrophobic porous substrate has an air permeability of 1000 seconds or less. <1> ~ <3> 2. A partition member for a total heat exchange element according to claim 1 . <5> The thickness of the hydrophobic porous substrate is 5 μm or more and 30 μm or less. <1> ~ <4> 2. A partition member for a total heat exchange element according to claim 1 . <6> The fine fibers are attached to the hydrophobic porous substrate. <1> ~ <5> A partition member for a total heat exchange element in any one of the above. <7> The coating weight of the fine fibers is 0.03 g / m 2 More than 3g / m 2 Is less than or equal to <1> ~ <6> 2. A partition member for a total heat exchange element according to claim 1 . <8> <1> ~ <7> A total heat exchange element partition member according to any one of claims 1 to 4, a spacer member arranged between the total heat exchange element partition members and spaced apart from the adjacent total heat exchange element partition members; A total heat exchange element having a first air flow path formed by a partition member for the total heat exchange element and the spacing member provided thereon, and a second air flow path formed by a partition member for the total heat exchange element that forms the first air flow path and the spacing member provided thereon. <9> A method for producing a partition member for a total heat exchange element, comprising coating a coating liquid containing fine fibers of polymeric polysaccharide having a fiber width of 1 to 1000 nm onto a hydrophobic porous substrate, followed by drying. <10> The coating liquid contains a surfactant <9> A method for producing the partition member for a total heat exchange element according to claim 1. <11> The coating weight of the fine fibers is 0.03 g / m 2 More than 3g / m 2 Is less than or equal to <9> or <10> A method for producing the partition member for a total heat exchange element according to claim 1. <12> The fine fibers have a fiber width of 1 to 10 nm. <9> ~ <11> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . <13> The fine fibers are fine cellulose fibers. <9> ~ <12> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . <14> The hydrophobic porous substrate has an air permeability of 1000 seconds or less. <9> ~ <13> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . <15> After subjecting the hydrophobic porous substrate to a surface hydrophilization treatment, the coating liquid is applied thereto. <9> ~ <14> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . Effect of the Invention
[0008] According to the present invention, there are provided a partition member for a total heat exchange element having excellent heat exchange efficiency, a total heat exchange element using the same, and a method for manufacturing a partition member for a total heat exchange element. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram illustrating the structure of a total heat exchange element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Partition material for total heat exchange element] The partition member for a total heat exchange element of the present invention (hereinafter also referred to as the partition member) contains a hydrophobic porous substrate (hereinafter also referred to as the substrate) and fine fibers of a polymeric polysaccharide having a fiber width of 1 to 1000 nm at least in the pores of the hydrophobic porous substrate, and has an air permeability of 10000 seconds or more and a moisture permeability of 2500 g / m 2 A partition member for a total heat exchange element having a durability of 24 hours or more.
[0011] In the present invention, "air permeability" is a value measured in accordance with the Oken air permeability method of JAPAN TAPPI paper pulp test method No. 5-2:2000. A preferable air permeability is 40,000 seconds or more. A larger air permeability value means a better gas barrier property.
[0012] In the present invention, the "moisture permeability" is measured in accordance with JIS Z 0208:1976. A higher moisture permeability value means a higher heat exchange efficiency. The preferred moisture permeability is 2800 g / m 2 24Hr or more, the preferred moisture permeability is 3000g / m 2 -24 hours or more.
[0013] The substrate to be used is not particularly limited, but preferably has a thickness of 5 μm to 30 μm, more preferably 10 to 25 μm. By making the thickness equal to or greater than the lower limit, the strength required as a partition member is maintained, and by making the thickness equal to or less than the upper limit, the heat exchange efficiency of sensible heat (temperature) is increased and weight reduction is possible. The thickness is a value measured in accordance with JIS P 8118:2014.
[0014] The surface density of the substrate is 29g / m 2 It is preferable that the thickness is 25 g / m or less. 2 More preferably, it is 20 g / m or less. 2 The lower limit is not particularly limited, and is 2 g / m or less. 2 More preferably, it is 5 g / m 2 That's all. The surface density of the hydrophobic porous substrate is a value obtained by measuring the weight per unit area.
[0015] The substrate is hydrophobic, so it can be made lighter. For example, if hydrophilic paper is used, it is necessary to coat a large amount of fine fibers of polymeric polysaccharides to improve the gas barrier properties, which makes it difficult to make the substrate lighter.
[0016] The air permeability of the substrate is preferably 1000 seconds or less. If the substrate is porous with an air permeability of 1000 seconds or less, latent heat (humidity) can be exchanged smoothly. The air permeability of the substrate is preferably 500 seconds or less. There is no particular restriction on the lower limit of the air permeability, but it is 10 seconds or more, preferably 30 seconds or more, and more preferably 50 seconds or more.
[0017] The substrate may be, for example, a film or nonwoven fabric made of a thermoplastic resin such as polyolefin or polyester, and has an air permeability of 1000 seconds or less, preferably 500 seconds or less.
[0018] In the present invention, the hydrophobic porous substrate contains fine fibers of polymeric polysaccharides having a fiber width of 1 to 1000 nm at least in the pores thereof so as to satisfy both the above-mentioned physical properties of air permeability and moisture permeability. The amount of the fine fibers of polymeric polysaccharides attached to the substrate (which can be rephrased as the coating amount) is not particularly limited, but is preferably 0.03 g / m 2 More than 3g / m 2 About 0.03 g / m or less, preferably 0.03 g / m 2 More than 2g / m 2 The following is the result. By attaching the hydrophilic material, the pores of the substrate can be blocked with the hydrophilic material, and the decrease in moisture permeability can be suppressed. When the amount of attached fine fibers of polymeric polysaccharide is large, the gas barrier property is excellent, but the moisture permeability tends to be impaired. 2 On the other hand, if the amount of the fine fibers of the polymeric polysaccharide attached is small, the pores are not sufficiently covered and sufficient gas barrier properties tend not to be obtained. 2 More preferably, it is equal to or greater than this.
[0019] The fine fibers of polymeric polysaccharides are not particularly limited as long as they are water-insoluble materials that form a film by adhering to a substrate and exhibit gas barrier properties. Examples of such materials include polymeric polysaccharides such as cellulose, chitin, and chitosan. Polymeric polysaccharides have a molecular structure with many hydroxyl groups (-OH), so they have a moisture absorbing effect, and the film they form has gas barrier properties. Among these, the use of fine fibers with a fiber width of 1 to 1000 nm can increase the air permeability and moisture permeability. Among these, a fiber width of 1 to 500 nm is preferred from the viewpoint of gas barrier properties, and a fiber width of 1 to 100 nm is more preferred. In particular, fine cellulose fibers are preferred because they form a dense structure when attached by coating and drying, and therefore have excellent gas barrier properties.
[0020] As the fine fibers of the polymeric polysaccharide, it is preferable to use fine cellulose fibers having a fiber width of 1 to 1000 nm. Among fine cellulose fibers, from the viewpoint of gas barrier properties, the fiber width is preferably 1 to 500 nm, more preferably 1 to 100 nm, further preferably 1 to 10 nm, and particularly preferably 1 to 10 nm. By making the fiber width of the fine cellulose fibers 1 nm or more, dissolution of the cellulose molecules in water is suppressed, and the effect of improving the air permeability and moisture permeability of the fine cellulose fibers is easily achieved.
[0021] The fiber width of the fine fibers of the polymeric polysaccharide is measured by observation under an electron microscope as follows. First, prepare an aqueous suspension of fine fibers of polymeric polysaccharides with a concentration of 0.05% by mass to 0.1% by mass, and cast this suspension onto a hydrophilized carbon film-coated grid to prepare a sample for TEM observation. If the sample contains wide fibers, it may be cast onto glass and the SEM image of the surface may be observed. Next, the image is observed using an electron microscope at a magnification of 1,000x, 5,000x, 10,000x, or 50,000x depending on the width of the fiber to be observed, with the sample, observation conditions, and magnification adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and 20 or more fibers intersect the line Y. For observation images that satisfy the above conditions, the width of the fibers intersecting with lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers intersecting with lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average fiber width is the average value of the fiber widths of the fine fibers of the polymeric polysaccharide that have been read.
[0022] The fiber length of the polymer polysaccharide fine fibers is not particularly limited, but is preferably 0.1 μm or more, and preferably 1,000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. By setting the fiber length of the polymer polysaccharide fine fibers within the above range, destruction of the crystalline region of the polymer polysaccharide fine fibers can be suppressed. In addition, it is possible to set the slurry viscosity of the polymer polysaccharide fine fibers within an appropriate range, making it easy to form a fiber layer. The fiber length of the fine fibers of the polymeric polysaccharide can be determined by image analysis using, for example, TEM, SEM, or AFM.
[0023] The axial ratio (fiber length / fiber width) of the fine fibers of the polymeric polysaccharide is not particularly limited, but is preferably at least 20, more preferably at least 50, and is preferably at most 10,000, more preferably at most 1,000. By setting the axial ratio within the above range, a slurry viscosity suitable for forming a fiber layer can be obtained.
[0024] In the present invention, it is preferable that at least one of ionic and nonionic groups is introduced into the fine fibers of the polymer polysaccharide. In addition, it is preferable that the ionic and nonionic groups are hydrophilic groups. From the viewpoint of improving the dispersibility of the fibers in the dispersion medium and increasing the defibration efficiency in the defibration treatment, it is more preferable that the fine cellulose fibers have an ionic group. The ionic group may include either one or both of an anionic group and a cationic group. In the present invention, it is particularly preferable that the ionic group has an anionic group. The anionic group is preferably at least one selected from a phosphate group or a group derived from a phosphate group, a phosphite group or a group derived from a phosphite group, a carboxy group or a group derived from a carboxy group, and a sulfonic acid group or a group derived from a sulfonic acid group.
[0025] The partition member for a total heat exchange element of the present invention contains a hydrophobic porous substrate and fine fibers of a polymeric polysaccharide having a fiber width of 1 to 1000 nm at least in the pores of the hydrophobic porous substrate, and has an air permeability of 10000 seconds or more and a moisture permeability of 2500 g / m2 The partition member for a total heat exchange element of the present invention has high air permeability and moisture permeability, has excellent carbon dioxide gas barrier properties, and is resistant to deterioration in mechanical strength even if condensation occurs. In addition, since it is lightweight, it is possible to increase the number of stacked layers of the total heat exchange element.
[0026] [Manufacturing method of partition members] The present invention provides a method for producing a partition member for a total heat exchange element, comprising coating a coating liquid containing fine fibers of polymeric polysaccharides having a fiber width of 1 to 1000 nm onto a hydrophobic porous substrate, followed by drying.
[0027] Details of the hydrophobic porous substrate and the fine fibers of polymeric polysaccharides are as described above. The polymer polysaccharide fine fibers are attached by coating. For example, a coating liquid containing the polymer polysaccharide fine fibers is applied to a hydrophobic porous substrate, followed by drying, whereby the polymer polysaccharide fine fibers can be attached. Regarding the coating method, a known coating machine can be used, and is not particularly limited, but a blade coater, a bar coater, a curtain coater, a die coater, an air knife coater, a roll coater, etc. can be used. Among them, a blade coater and a bar coater are preferred because the pressing force of the blade or bar during coating causes the coating liquid to penetrate into the pores of the porous substrate. For drying, a dryer attached to the coater can be used. The drying temperature is preferably a surface temperature of 90° C. or less, more preferably 80° C. or less. Drying at high temperatures may cause bumping of the coating liquid. The coating liquid containing fine fibers of polymeric polysaccharides may be applied to at least one surface of the hydrophobic porous substrate.
[0028] The amount of fine fibers of polymeric polysaccharide attached is 0.03g / m 2 More than 3g / m 2 If the amount is less than 3 g / m, a homogeneous coating film can be formed, the pores of the substrate can be blocked with the hydrophilic material, and the decrease in moisture permeability can be suppressed. If the amount of fine fibers of polymeric polysaccharide attached is large, the gas barrier property is excellent, but the moisture permeability tends to be impaired. 2On the other hand, if the amount of the fine fibers of the polymeric polysaccharide attached is small, sufficient gas barrier properties tend not to be obtained, and the amount of attachment is preferably 0.03 g / m or less. 2 More preferably, it is equal to or greater than this. Applying fine fibers of polymeric polysaccharides by coating is preferable because it increases moisture permeability, possibly because the fine fibers of polymeric polysaccharides penetrate not only into the surface of the hydrophobic porous substrate but also into the interior of the pores.
[0029] When applying a coating liquid containing fine fibers of polymeric polysaccharides to a hydrophobic porous substrate, if the substrate repels the coating liquid, it is advisable to add a surfactant, a wetting agent, a leveling agent, etc. to the coating liquid, or to subject the substrate to a surface hydrophilization treatment such as corona discharge treatment in advance, or to use these in combination. If repelling occurs during application, it tends not to be possible to obtain a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more. It is preferable to use surfactants, wetting agents, leveling agents, etc. that have reduced foaming properties.
[0030] Since the amount of fine fibers of polymeric polysaccharide attached to the partition member of the present invention is small, latent heat (humidity) heat exchange is performed even without the attachment of a moisture absorbent, but a moisture absorbent may be blended to further increase moisture permeability. Examples of moisture absorbents include inorganic acid salts, organic acid salts, polyhydric alcohols, and ureas. For example, inorganic acid salts include lithium chloride, calcium chloride, and magnesium chloride. Examples of organic acid salts include sodium lactate, calcium lactate, and sodium pyrrolidone carboxylate. Examples of polyhydric alcohols include glycerin, ethylene glycol, triethylene glycol, and polyglycerin. Examples of ureas include urea and hydroxyethyl urea.
[0031] In addition, the coating liquid may contain auxiliary agents such as preservatives, antifungal agents, flame retardants, viscosity adjusters, pH adjusters, colorants, storage improvers, and polymer resins, as long as the effects of the present invention are not impaired.
[0032] When applying the coating solution containing fine fibers of polymeric polysaccharides, the amount of the coating is adjusted so that the resulting partition member for a total heat exchange element has an air permeability of 10,000 seconds or more. 2 It is preferable to adjust the amount of adhesion so that it lasts for 24 hours or more.
[0033] [Total heat exchange element] The total heat exchange element of the present invention is a total heat exchange element using the heat exchange element partition member of the present invention. That is, the total heat exchange element includes a plurality of the total heat exchange element partition members and a spacing member disposed between the total heat exchange element partition members to maintain a spacing between the adjacent total heat exchange element partition members, and has a first air flow path formed by the total heat exchange element partition members and the spacing member provided thereon, and a second air flow path formed by the total heat exchange element partition members forming the first air flow path and the spacing member provided below them.
[0034] Hereinafter, the total heat exchange element will be described with reference to FIG. 1, however, the present invention is not limited to the total heat exchange element having the structure of FIG. Fig. 1 is a schematic diagram illustrating the structure of a total heat exchange element 10. As shown in Fig. 1, the total heat exchange element 10 is composed of a plurality of partition members 1 and a plurality of spacing members 2 that form air flow paths between the plurality of partition members 1 and maintain the spacing between the partition members 1. The partition member 1 is a flat plate having a square or diamond shape.
[0035] [Spacing member] The spacing member is not particularly limited as long as it maintains the spacing between the partition members. The spacing member maintains the spacing between the partition members, thereby forming the plurality of partition members and air flow paths between the plurality of partition members. The spacing member 2 is, for example, a corrugated plate formed into a sawtooth or sinusoidal wave shape whose projected planar shape matches the shape of the partition member 1. The spacing member 2 is shaped, for example, like the core of a cardboard box, and is formed by corrugating. The spacing member is not limited to a corrugated material such as a paper substrate, a film, or a nonwoven fabric, but may be a resin rib. Among them, a paper substrate is preferable. Since a paper substrate has a moisture-regulating function, it can compensate for the decrease in the moisture-regulating function of a partition member using a hydrophobic porous substrate.
[0036] The ridges and valleys of the wave shape of the spacing member 2 are joined to the partition member 1 by an adhesive or the like. The spacing member 2 is joined to the partition member 1 on one surface of the partition member 1 with the direction of the wave shape ridges extending in a first direction (e.g., vertical direction), and is joined to the partition member 1 on the other surface with the direction of the wave shape ridges extending in a second direction (e.g., horizontal direction). That is, in two adjacent spacing members 2 sandwiching the partition member 1, the spacing members 2 are stacked alternately across the partition member 1 so that the direction of the wave shape ridges of the spacing member 2 joined to one surface, i.e., the first air flow path, is perpendicular to the direction of the wave shape ridges of the spacing member 2 joined to the other surface, i.e., the second air flow path.
[0037] Between the spacing member 2, whose corrugated ridge lines are oriented in a first direction (e.g., vertical direction), and the partition members 1 on both sides, a plurality of first air flow paths 4 are formed along the first direction. Furthermore, between the spacing member 2, whose corrugated ridge lines are oriented in a second direction (e.g., horizontal direction), and the partition members 1 on both sides, a plurality of second air flow paths 5 are formed along the second direction. Note that arrow 6 in Fig. 1 indicates the air flow direction in the first air flow path 4, and arrow 7 in Fig. 1 indicates the air flow direction in the second air flow path 5.
[0038] Since the spacing members 2 whose corrugated ridgelines are oriented in a first direction and the spacing members 2 whose corrugated ridgelines are oriented in a second direction are alternately stacked with the partition member 1 in between so that the ridgeline directions are perpendicular to each other, the extension direction of the first air flow path 4 and the extension direction of the second air flow path 5 are also perpendicular to each other. For example, supply air is ventilated through the first air flow path 4, and exhaust air is ventilated through the second air flow path 5, and heat is exchanged between the supply air and the exhaust air via the partition member 1 and the spacing members 2. 1, the spacing member 2 is provided so as to be perpendicular to the first air flow path and the second air flow path. However, it is not necessary to dispose the spacing member 2 so as to be perpendicular to the first air flow path and the second air flow path, and it is sufficient that the spacing members 2 are arranged in different directions, such as facing each other.
[0039] The method for joining the partition member and the spacing member can be a known method such as a method using an adhesive or a thermal bonding method without using an adhesive. Among them, the method using an adhesive is preferable because it can firmly bond the spacing member and the partition member. As the adhesive, a known adhesive such as a polyvinyl alcohol adhesive or an ethylene vinyl acetate adhesive can be used. EXAMPLES
[0040] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0041] <Preparation of the substrate> Substrate A: A 20 μm thick polyethylene film (product name: SW320H, manufactured by Shenzhen Senior Technology Material Co., Ltd.) was prepared as a hydrophobic porous substrate. The surface density was 10.0 g / m 2 It was. Substrate B: A 16 μm thick polypropylene film (product name: SD216101+, manufactured by Shenzhen Senior Technology Material Co., Ltd.) was prepared as a hydrophobic porous substrate. The surface density was 9.4 g / m 2 It was.
[0042] Example 1 <Production of fine cellulose fiber A> (Phosphate group introduction step) The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 210 g / m) manufactured by Oji Paper Co., Ltd. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 690 ml when disintegrated and measured in accordance with JIS P 8121:2012) was used. This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to the raw pulp to adjust the ratio of ammonium dihydrogen phosphate to 45 parts by mass, urea to 120 parts by mass, and water to 150 parts by mass per 100 parts by mass (bone dry mass) of raw pulp, to obtain a chemical-impregnated pulp. The chemical-impregnated pulp was then heated for 200 seconds in a hot air dryer at 165°C to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0043] (Cleaning process) The resulting phosphorylated pulp was then subjected to a washing treatment. The washing process was carried out by pouring 10 L of ion-exchanged water per 100 g (bone dry weight) of phosphorylated pulp, stirring to uniformly disperse the pulp, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0044] (Alkaline treatment process) Next, the washed phosphorylated pulp was subjected to an alkali treatment (neutralization treatment) as follows. First, the washed phosphorylated pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain phosphorylated pulp that had been subjected to an alkali treatment (neutralization treatment). Next, the phosphorylated pulp after the alkali treatment was subjected to the above-mentioned washing treatment. The infrared absorption spectrum of the phosphorylated pulp obtained after the alkali treatment was measured using FT-IR. -1Absorption due to phosphate groups was observed in the vicinity, confirming that phosphate groups had been added to the pulp. In addition, the obtained phosphorylated pulp was analyzed using an X-ray diffraction device, and typical peaks for cellulose type I crystals were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0045] (Fibrillation process) Ion-exchanged water was added to the phosphorylated pulp obtained through the above-mentioned alkali treatment process to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated three times at a pressure of 200 MPa in a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine cellulose fiber dispersion liquid containing fine cellulose fiber A. X-ray diffraction confirmed that this fine cellulose fiber A maintained cellulose type I crystals. In addition, the fiber width of the fine cellulose fiber A was measured using a transmission electron microscope and was found to be 3 to 5 nm.
[0046] <Manufacture of Partition Members for Total Heat Exchange Elements> To 99.2 parts of the resulting 0.4% aqueous dispersion of fine cellulose fibers A, 0.8 parts of a polyether surfactant (product name: SN Wet 985, manufactured by San Nopco, 76% aqueous dispersion) was added to prepare a coating liquid. One side of the substrate A was subjected to a corona discharge treatment, and then the coating liquid was applied to the substrate using a Mayer bar so that the adhesion amount (coating amount) of the fine cellulose fiber A after drying was 0.03 g / m 2 The coating was then dried to obtain a partition member for a total heat exchange element.
[0047] Example 2 In the production of the partition member for the total heat exchange element of Example 1, the adhesion amount (coating amount) of the fine cellulose fiber A after drying was 0.08 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the coating and drying were carried out so that the coating composition was such that the thickness of the coating film was 100 μm or more and the thickness of the coating film was 100 μm or more.
[0048] Comparative Example 1 The substrate A was used as it was as a partition member for the total heat exchange element.
[0049] Comparative Example 2 In the production of the partition member for the total heat exchange element of Example 1, the adhesion amount (coating amount) of the fine cellulose fiber A after drying was 0.02 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the coating and drying were carried out so that the coating composition was such that the thickness of the coating film was 100 μm or more and the thickness of the coating film was 100 μm or more.
[0050] Example 3 A partition member for a total heat exchange element of Example 1 was obtained in the same manner as in Example 1, except that the following was performed in the production of the partition member for a total heat exchange element of Example 1.
[0051] <Manufacture of Partition Members for Total Heat Exchange Elements> To 99.2 parts of the 0.4% aqueous dispersion of the fine cellulose fibers A obtained above, 0.8 parts of a polyether surfactant (product name: SN Wet 985, manufactured by San Nopco, 76% aqueous dispersion) was added to prepare a coating liquid. The coating liquid was applied to one surface of the substrate A using a Mayer bar so that the adhesion amount (coating amount) of the fine cellulose fiber A after drying was 0.17 g / m 2 The coating was then dried to obtain a partition member for a total heat exchange element.
[0052] Example 4 In Example 1, the substrate A was changed to the substrate B. Furthermore, the adhesion amount (coating amount) of the fine cellulose fiber A after drying was 0.09 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the coating and drying were carried out so that the coating composition was such that the thickness of the coating film was 100 μm or more and the thickness of the coating film was 100 μm or more.
[0053] Comparative Example 3 Substrate B was used as it was as a partition member for the total heat exchange element.
[0054] Example 5 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the following was performed in Example 1.
[0055] <Production of fine cellulose fiber B> (Fibrillation process) Ion-exchanged water was added to the phosphorylated pulp obtained through the above-mentioned alkali treatment process to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine cellulose fiber dispersion liquid containing fine cellulose fiber B. X-ray diffraction confirmed that this fine cellulose fiber B maintained cellulose type I crystals. In addition, when the fiber width of fine cellulose fiber B was measured using a transmission electron microscope, it was confirmed that the fiber width was 3 to 500 nm.
[0056] <Manufacture of Partition Members for Total Heat Exchange Elements> The 0.4% dispersion of the fine cellulose fibers B obtained above was used as a coating liquid. After one surface of the substrate A was subjected to a corona discharge treatment, the coating liquid was applied with a Mayer bar to a substrate having a coating weight (coating weight) of 0.28 g / m2 after drying. 2 The coating was then dried to obtain a partition member for a total heat exchange element.
[0057] Example 6 In Example 5, the adhesion amount (coating amount) of the fine cellulose fiber B after drying was 0.10 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 5, except that the coating and drying were carried out so that the coating composition was such that the thickness of the coating film was 100 μm or more and the thickness of the coating film was 100 μm or more.
[0058] Example 7 In Example 5, the substrate was changed to substrate B. Furthermore, the adhesion amount (coating amount) of the fine cellulose fiber B after drying was 0.28 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 5, except that the coating and drying were carried out so that the coating composition was such that the thickness of the coating film was 100 μm or more and the thickness of the coating film was 100 μm or more.
[0059] (evaluation) The moisture permeability and air permeability of the partition members for a total heat exchange element obtained in the examples and comparative examples were measured and are shown in Tables 1 and 2. "Moisture permeability" Measurements were performed under conditions of 20°C and 65% RH in accordance with JIS Z0208:1976, with the exception that calculations were performed using the following formula: Moisture permeability=(a+b) / 2 Here, a = mass increment after 1 hour of measurement b = Mass increase per hour from 1 hour after the start of measurement to 2 hours after the start of measurement
[0060] "Air permeability" Measurements were taken in accordance with the Oken air permeability method of JAPAN TAPPI Paper and Pulp Test Method No. 5-2:2000.
[0061] "Carbon dioxide gas barrier properties" A 12cm square partition member was prepared, and high-concentration CO2 was used as a test sample. Container A was used to measure the CO2 concentration, and container B was used to constantly ventilate the outside air. The partition member was placed between container A and container B. Container A was filled with 20,000 ppm of CO2 under normal temperature and pressure conditions, and then left for 15 minutes. The CO2 concentration in container A was then measured using a CO2 analyzer. The amount of CO2 that passed through the partition member in 15 minutes was calculated as the decrease in CO2 concentration in container A. When the CO2 concentration in container A was 2500 ppm or more, the carbon dioxide gas barrier properties of the partition member were judged to be good and marked with a circle, and when it was less than 2500 ppm, it was judged to be poor and marked with a cross. The evaluation results are shown in Tables 1 and 2 below.
[0062] [Table 1]
[0063] [Table 2] [Explanation of symbols]
[0064] 1 Partition member 2 Spacing members 4 First air flow path 5 Second Air Flow Path 10 Total heat exchange element
Claims
1. A hydrophobic porous substrate; The hydrophobic porous substrate contains fine fibers of polymeric polysaccharides having a fiber width of 1 to 1000 nm at least in the pores thereof, The air permeability is 10,000 seconds or more, and the moisture permeability under the conditions of 20°C and 65% RH is 2,500 g / m 2 A partition member for a total heat exchange element having a life of 24 hours or more.
2. 2. The partition member for a total heat exchange element according to claim 1, wherein the fine fibers are fine cellulose fibers.
3. 2. The partition member for a total heat exchange element according to claim 1, wherein the fine fibers have a fiber width of 1 to 10 nm.
4. 2. The partition member for a total heat exchange element according to claim 1, wherein the hydrophobic porous substrate has an air permeability of 1000 seconds or less.
5. 5. The partition member for a total heat exchange element according to claim 4, wherein the hydrophobic porous substrate has a thickness of 5 [mu]m or more and 30 [mu]m or less.
6. 2. The partition member for a total heat exchange element according to claim 1, wherein the fine fibers are attached to the hydrophobic porous substrate.
7. The coating amount of the fine fibers is 0.03 g / m 2 3g / m or more 2 7. The partition member for a total heat exchange element according to claim 6, wherein:
8. A heat exchanger according to any one of claims 1 to 7, a spacer member arranged between the total heat exchange element partition members and spaced apart from the adjacent total heat exchange element partition members; A total heat exchange element having a first air flow path formed by a partition member for the total heat exchange element and the spacing member provided thereon, and a second air flow path formed by a partition member for the total heat exchange element that forms the first air flow path and the spacing member provided below it.
9. The method for producing a partition member for a total heat exchange element comprises coating a coating liquid containing fine fibers of a polymeric polysaccharide having a fiber width of 1 to 1000 nm onto a hydrophobic porous substrate, followed by drying.
10. The method for producing a partition member for a total heat exchange element according to claim 9, wherein the coating liquid contains a surfactant.
11. A coating liquid containing the fine fibers is applied, and the coating amount of the fine fibers is 0.03 g / m 2 3g / m or more 2 The method for producing a partition member for a total heat exchange element according to claim 9, wherein the following is performed.
12. The method for producing a partition member for a total heat exchange element according to claim 9, wherein the fine fibers have a fiber width of 1 to 10 nm.
13. The method for producing a partition member for a total heat exchange element according to claim 9, wherein the fine fibers are fine cellulose fibers.
14. The method for producing a partition member for a total heat exchange element according to claim 9, wherein the hydrophobic porous substrate has an air permeability of 1000 seconds or less.
15. 10. The method for producing a partition member for a total heat exchange element according to claim 9, wherein the coating liquid is applied to the hydrophobic porous substrate after the substrate is subjected to a surface hydrophilization treatment.
Citation Information
Patent Citations
Sheet for total heat exchangers, element for total heat exchangers, and total heat exchanger
WO2019026823A1
Total heat exchange device paper
JP2021155865A
Total heat exchange element paper
JP4252892B2